Close substellar-mass companions in stellar wide binaries: discovery and characterization with APOGEE and Gaia DR2. Issue 3 (16th August 2021) - Lewis, Hannah M; Anguiano, Borja; Majewski, Steven R; Nidever, David L; Badenes, Carles; De Lee, Nathan; Hasselquist, Sten; Mazzola Daher, Christine; Stassun, Keivan G; Bizyaev, Dmitry; Godoy-Rivera, Diego; Nitschelm, Christian; et al.
ABSTRACT: We present a search for close, unresolved companions in a subset of spatially resolved Gaia wide binaries containing main-sequence stars within 200 pc of the Sun, utilizing the APOGEE– Gaia Wide Binary Catalog. A catalogue of 37 wide binaries was created by selecting pairs of stars with nearly identical Gaia positions, parallaxes, and proper motions, and then confirming candidates to be gravitationally bound pairs using APOGEE radial velocities. We identify close, unresolved stellar and substellar candidate companions in these multiple systems using (1) the Gaia binary main sequence and (2) observed periodic radial velocity variations in APOGEE measurements due to the influence of a close substellar-mass companion. The studied wide binary pairs reveal a total of four stellar-mass close companions in four different wide binaries, and four substellar-mass close companion candidates in two wide binaries. The latter are therefore quadruple systems, with one substellar-mass companion orbiting each wide binary component in an S-type orbit. Taken at face value, these candidate systems represent an enhancement of an order of magnitude over the expected occurrence rate of ∼2 per cent of stars having substellar companions >2 MJup within ∼100-d orbits; we discuss implications and possible explanations for this result. Finally, we compare chemical differences between the components of the wide binaries and the components of the candidate higher-order systems and find that any chemical influence or correlation due to the presence of close companions to wide binary stars is not discernible.